Arctic Tundra Habitat Emergency Conservation Act : report (to accompany H.R. 2454) (including cost estimate of the Congressional Budget Office). - United States. Congress. House. Committee on Resources. ([Washington, D.C. : U.S. G.P.O., 1999)
"July 29, 1999." Shipping list no.: 99-0337-P. Distributed to some depository libraries in microfiche. Caption title. Mode of access: Internet.